The Relationship Family Support and Anxiety on Quality of Life in Stroke Patients - Santosa, Winanda Rizki Bagus; Akasyah, Wildan; Pratama, Yuan Guruh (Indonesian Journal Publisher, 2025)
Stroke is a major cause of mortality and disability in the world. In addition to physical post-stroke problems, psychosocial issues including anxiety and family support significantly affect stroke patients' quality of life. The purpose of this study is to ascertain how anxiety and family support affect stroke patients' quality of life. Methods: This research is quantitative. The research design used in this study is cross-sectional. Questionnaires about anxiety, quality of life, and family support were used to gather data. 58 stroke patients who satisfied the inclusion and exclusion criteria were chosen for this study using a total sample technique. This investigation was carried out in the Stroke Room at X Hospital in Blitar between February 24 and March 24, 2025. The Spearman rho correlation test was employed by the researchers. Results: According to 18 respondents (31.1%), the majority of families did not help stroke patients, and they had a low quality of life. There is a correlation between stroke patients' quality of life and family support, as indicated by the P-value of 0.001 and rho of 0.239. Thirteen respondents (22.3%) reported having a low quality of life and experiencing extreme anxiety. A P-value of 0.012 and a rho of 0.124 indicated a correlation between anxiety and quality of life. Conclusion: Anxiety levels and family support can have an impact on stroke patients' quality of life. While high levels of anxiety might lower a patient's quality of life, strong levels of family support can enhance it.